Efektivitas Kegiatan Ahad Mengaji Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Masyarakat Desa Gohor Lama - Khairunisa, Yunda; Nasution, Abdul Fattah (EduInovasi: Journal of Basic Educational Studies, 2024)
As Muslims, should be able to read the quran properly and correctly to make it easier to understand the teachings of our own religion and carry out our religious activities. The problem is that there are still many Muslims who cannot read the qur’an properly and correctly. Therefore the researcher is interested in raising this problem as a study with the formulation of the problem how the effectiveness of Sunday Koran activities in improving the ability to read the qur’an in the village of Gohor Lama, what activities are included in Sunday Koran activities, what are the obstacles in carrying out Sunday qur’an activities. With the aim of research to find out how effectiveness, programs, and obstacles are felt when carrying out this Sunday qur’an program. The benefit of this research is to develop the author's knowledge as an effort to complete the final project, as well as to increase knowledge in the community and as a means of criticizing the Sunday qur’an program. This study uses descriptive qualitative research methods with data collection techniques of observation, interviews and literature studies with data analysis techniques of data collection, data reduction, data display, and drawing conclusions. The results of this study are that the Sunday qur’an activity is effective in improving the ability to read the qur’an in the village of Gohor Lama. This research contributes in the form of socializing Sunday qur’an activities to people. who have not participated in Sunday qur’an activities.